2011
DOI: 10.1016/j.ijdevneu.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of birth asphyxia on neonatal hippocampal structure and function in the spiny mouse

Abstract: Studies of human neonates, and in animal experiments, suggest that birth asphyxia results in functional compromise of the hippocampus, even when structural damage is not observable or resolves in early postnatal life. The aim of this study was to determine if changes in hippocampal function occur in a model of birth asphyxia in the precocial spiny mouse where it is reported there is no major lesion or infarct. Further, to assess if, as in human infants, this functional deficit has a sex-dependent component. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…A decrease of LTP has been shown in hippocampal slices obtained 3 and 7 days after IH in adult rats (Payne et al, 2004) and LTP was proportionally lower in adult mice IH after 3 and 14 days of 10% oxygen 90 s cycle IH (Xie et al, 2010) that could be rescued by exogenous BDNF. There is a paucity of data in LTP changes after neonatal IH and neonatal hypoxia‐ischemia, but a decrease of LTP had been found postnatally in spiny mice 5 days after near term acute fetal asphyxia (Fleiss et al, 2011) in the model associated with postnatal behavioral abnormalities (Ireland et al, 2010). Of interest, there was no structural injury observed in this model, but neuronal density and synaptophysin expression and BDNF were increased in hippocampus in male P5 pups, suggesting that the behavioral changes were likely due to changes in synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of LTP has been shown in hippocampal slices obtained 3 and 7 days after IH in adult rats (Payne et al, 2004) and LTP was proportionally lower in adult mice IH after 3 and 14 days of 10% oxygen 90 s cycle IH (Xie et al, 2010) that could be rescued by exogenous BDNF. There is a paucity of data in LTP changes after neonatal IH and neonatal hypoxia‐ischemia, but a decrease of LTP had been found postnatally in spiny mice 5 days after near term acute fetal asphyxia (Fleiss et al, 2011) in the model associated with postnatal behavioral abnormalities (Ireland et al, 2010). Of interest, there was no structural injury observed in this model, but neuronal density and synaptophysin expression and BDNF were increased in hippocampus in male P5 pups, suggesting that the behavioral changes were likely due to changes in synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…White matter injury is a consistent finding in perinatal brain hypoxia and ischemia injury of different types (Cai et al, 2012; Juliano et al, 2015; Darnall et al, 2017; Oorschot et al, 2013) and may also be a determinant of later cognitive abnormalities. Impairments in LTP have been examined in models of single acute hypoxic event during prenatal period (Fleiss et al, 2011), but have not been studied in neonatal IH, especially in relation to cognitive outcome. We hypothesize that brief but multiple episodes of severe desaturation accompanied by bradycardia will affect synaptic plasticity and be sufficient to produce long‐term cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Many cognitive impairments and memory losses occur by hypoxic brain injury after cardiac arrest, but the precise mechanism of this phenomenon is not yet clearly proven (6). Fleiss et al (7) reported that hypoxic brain injury in an animal model of birth asphyxia produced significant functional deficits in the hippocampus, and caused a reduction of long-term potentiation (LTP), paired pulse facilitation (PRF), and post-tetanic potentiation (PTP). This occurred in the absence of gross cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was made for glial fibrillary acidic protein (GFAP), ionized calcium binding adaptor molecule 1 (Iba1), myelin basic protein (MBP), and microtubule-associated protein 2 (MAP2) using densitometric analysis, as previously described [31,32] using Image J (NIH, USA). Counts were made of CD68, CD45, Ki67, Olig2, NeuN, Calbindin and BrdU.…”
Section: Methods and Animalsmentioning
confidence: 99%
“…Figure 2 demonstrates brain regions evaluated with IHC staining. Analyses were made in 3 fields of view (FOV) per brain region for densitometric analysis and 2 FOV per brain region for counts as previously described [31,32]. IHC data across fields of view were averaged and the mean used in statistical analyses in Graphpad prism (version 5 for Mac).…”
Section: Methods and Animalsmentioning
confidence: 99%